Seasonal Ground Movement Due to Swelling/Shrinkage of Nicosia Marl - Ploutarchos Tzampoglou; Dimitrios Loukidis; Niki Koulermou (Remote Sensing, 2022)
This research investigates the seasonal ground heave/settlement of an area covered by an expansive soil of Cyprus called Nicosia marl, highlighting the degree of influence of the main causal factors. For this purpose, existing geotechnical data from the archives of the Cyprus Geological Survey were first collected and processed to compile maps of the key geotechnical parameters in the study area. In order to estimate the ground movements in the area, Earth Observation (EO) techniques for the period between 16 November 2002–30 December 2006 were processed. The correlation of these movements with the existing geotechnical data indicates that there is a statistically significant correlation between plasticity index and the ground movements. Multivariate linear regression analysis using Lasso revealed that the plasticity index ranks first in importance among the examined variables.